2006
DOI: 10.1037/0022-0167.53.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the self-stigma associated with seeking psychological help.

Abstract: Self-stigma is an important factor in people's decisions not to engage in therapy. To measure this construct, the authors developed the 10-item Self-Stigma of Seeking Help (SSOSH) scale. In Study 1 (n ϭ 583), the SSOSH had a unidimensional factor structure and good reliability (.91) among participants. Study 2 (n ϭ 470) confirmed the factor structure. Studies 2, 3 (n ϭ 546), and 4 (n ϭ 217) cross-validated the reliability (.86 to .90; test-retest, .72) and showed evidence of validity (construct, criterion, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
1,318
2
36

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 942 publications
(1,410 citation statements)
references
References 56 publications
54
1,318
2
36
Order By: Relevance
“…This heightened attention is, in part, due to the important associations between stigma and the severity of mental illness symptoms (Andrade et al 2014;Brown 2017;Drapalski et al 2013), disclosure of conditions to friends, family, and healthcare professionals (Dew et al 2007;Donnelly 2017;Prior et al 2003), self-esteem (Corrigan 2004;Corrigan and Watson 2002;Corrigan, Watson, and Barr 2006), and treatment-seeking behavior (Clement et al 2015;Tsang, Fung, and Chung 2010;Vogel, Wade, and Haake 2006). While population estimates suggest that many individuals with symptoms of mental illness do not receive treatment or are undertreated Wang et al 2005Wang et al , 2007, scholars, healthcare providers, and other stakeholders hope that stigma reduction efforts will increase treatment-seeking behavior (Clair, Daniel, and Lamont 2016;Hatzenbuehler, Phelan, and Link 2013;Hunter et al 2017;Pilgrim and Rogers 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This heightened attention is, in part, due to the important associations between stigma and the severity of mental illness symptoms (Andrade et al 2014;Brown 2017;Drapalski et al 2013), disclosure of conditions to friends, family, and healthcare professionals (Dew et al 2007;Donnelly 2017;Prior et al 2003), self-esteem (Corrigan 2004;Corrigan and Watson 2002;Corrigan, Watson, and Barr 2006), and treatment-seeking behavior (Clement et al 2015;Tsang, Fung, and Chung 2010;Vogel, Wade, and Haake 2006). While population estimates suggest that many individuals with symptoms of mental illness do not receive treatment or are undertreated Wang et al 2005Wang et al , 2007, scholars, healthcare providers, and other stakeholders hope that stigma reduction efforts will increase treatment-seeking behavior (Clair, Daniel, and Lamont 2016;Hatzenbuehler, Phelan, and Link 2013;Hunter et al 2017;Pilgrim and Rogers 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Stigma and discrimination associated with mental illness are common (Angermeyer & Dietrich, 2006;Rose et al 2011;Schomerus et al 2012b;Lasalvia et al 2013) and can act as barriers to helpseeking and prevention in different ways (Corrigan & Rüsch, 2002;Phelan et al 2006;Schomerus & Angermeyer, 2008;Clement et al 2012;Lanfredi et al 2013). People with mental illness may avoid helpseeking due to fear of being discriminated against by others (public stigma) or because they agree with negative stereotypes and turn them against themselves (self-stigma) (Vogel et al 2006;Rüsch et al 2009a;Evans-Lacko et al 2012). Shame about one's mental illness is strongly related to self-stigma and can therefore be considered self-stigma's emotional side (Rüsch et al 2006(Rüsch et al , 2007b.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon the discussions about societal stigma toward mental illness, public stigma toward mental health treatment has been understood as "label avoidance" (Corrigan 2004, p. 616): that individuals may avoid seeking professional services due to the fear of being labeled as the stigma-attached "mentally ill" (Clement et al 2015). Self-stigma on the other hand addresses the beliefs that seeking professional help would lead to the acknowledgement of one's weakness, inferiority, or failure, and thus threaten one's selfesteem (Corrigan 2004;Fisher et al 1982;Vogel et al 2006). Courtesy stigma signifies the beliefs that individuals or communities would be downgraded by geographically or socially closely associating with those seeking mental health treatment or mental health facilities.…”
Section: Beliefs and Experiences Of Seeking Help: Beliefs About Healimentioning
confidence: 99%
“…Self-stigma: Building on Scheff (1966)'s discussion of individuals' internalization of cultural stereotypes of mental illness, Link (1987) summarized two negative consequences that might arise through individuals' association with mental health institutions, premised upon the largely negative images of mental illness and mental services in Western culture and beyond: First, individuals may devalue themselves since they are now officially falling into an institutional category that is negatively viewed by the public, and second, individuals may develop defensive or other negative social actions and interactions due to internalized concerns of how others may think of them. As for the former, studies have shown that in fear of losing self-esteem, self-efficacy, or self-autonomy, individuals might choose not to seek professional assistance despite the fact that they are suffering mental distress (Miller 1985;Nadler 1986a, b;Vogel et al 2006). As for the latter, individuals might avoid services or even rearrange their lives because of feelings of shame, embarrassment, or guilt that could be invoked by fear that others would find out that they are receiving services .…”
Section: Beliefs and Expectations About The Efficacy Of Professionalmentioning
confidence: 99%